Current Issues and Future Direction in Kidney Transplantation - Rath, Thomas (IntechOpen, 2013)
The here presented book covers different areas of clinical and scientific interest, reaching from donor evaluation to newest methods in immunological diagnostics. But also aspects of daily care of transplant recipients can be found in the carefully selected chapters. Everything driven by the aim to improve the care for all of our transplanted patients.